Health Education and Early Screening for Gout Arthritis in Garut City District - Genialita Fadhilla; Sitti Fatimah; Hannina Lidina; Harlena Pratama (Indonesian Journal of Community Empowerment (IJCE), 2026)
Gout arthritis is a non-communicable disease caused by hyperuricemia, with increasing prevalence due to aging, lifestyle changes, and limited public knowledge on prevention and early detection. This activity aimed to improve community knowledge and conduct uric acid screening to support early prevention in Garut City District. Methods included interactive health education, uric acid testing using the Easy Touch GCU device, and pre-test and post-test evaluation among 30 participants. Results showed that 23,3% had high uric acid levels and 33,3% had a history of gout arthritis. Knowledge significantly improved after the intervention, with good knowledge increasing from 20% to 80%. The Wilcoxon test indicated a significant difference before and after education (p < 0,05). This activity effectively improved community awareness and supports preventive and promotive efforts for gout arthritis through education and early detection.